Image Reconstruction and Resolution via Electrical Impedance Tomography - ., Vyner V Raya (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Electrical Impedance Tomography (EIT) is the cheapest imaging method known but with a questionable ability to produce reliable image. Improving the resolution and the quality of the reconstructed image will be the ultimate aim of this project. Image of better quality is achievable with the incremental number of electrodes used. A better image quality is possible with the utilization of a finer-meshed Finite Element Model (FEM) in solving forward problem of the algorithm involves. Further improvement on the images is attainable with the application of image post-processing of Matlab, in which an image of better contrast and noise-free is reconstructed. We are now one step closer in establishing EIT as a reliable imaging technique in the future.